Reducing Waste Volume from Cafeteria Activities by 50% into Compost at AMM ABP Kutai Kartanegara Site-East Kalimantan - Budiman*, Arif; Fathoni, Naim; Nadeak, Ali Amran; Putri, Amalia Mustikasari (Riwayat: Educational Journal of History and Humanities, 2023)
The increasing volume of waste from canteen activities at the AMM ABP Kutai Kartanegara site is a serious environmental problem. Therefore, a solution is needed to reduce the negative impact. This study aims to reduce the volume of canteen waste by 50% and convert it into compost that can be used to support agriculture around the site. This research uses an experimental method by conducting a composting process on canteen waste. Data were collected through direct observation and literature study. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the composting process can reduce the volume of canteen waste by 50% and produce quality compost. Waste management from canteen activities has an impact on reducing the volume of mine waste every month by separating inorganic and organic waste. The separated organic waste is processed into compost at a cost of Rp. 105,000 per month for the purchase of Effective Microorganism (EM4) bacteria at Rp. 35,000/bottle. In one month, 340 kg of compost fertilizer is produced.